1986
DOI: 10.1289/ehp.866683
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of cotton workers in an experimental cardroom with reference to airborne endotoxins.

Abstract: Workers from cotton mills were exposed to cotton dust during carding in an experimental cardroom. Cotton from different geographical locations with varying amounts of endotoxin were used. Exposure levels ranged from 0.6 to 3.6 mg dust/m3 (from a vertical elutriator) and from 0.1 to 8.0 ,ug/m3 of endotoxin.No relationship was found between the decrease in FEV1 over the workshift and the amount of airborne dust. Airborne endotoxin correlated with the decrease in FEV,and the increase in blood neutrophils. The FEV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Historically, however, the study of organic dust-related disease has focused on acute airway responses, including chest tightness, cross-shift drops in forced expiratory volume in 1 s (FEV 1 ), and airway hyperresponsiveness. These acute airway responses may even be observed in healthy volunteers exposed for a short time in model cardrooms (52), or when exposed to extracts of grain dust (53). However, manifestations of a COPD-like presentation can appear after several years of exposure (5).…”
Section: Discussionmentioning
confidence: 99%
“…Historically, however, the study of organic dust-related disease has focused on acute airway responses, including chest tightness, cross-shift drops in forced expiratory volume in 1 s (FEV 1 ), and airway hyperresponsiveness. These acute airway responses may even be observed in healthy volunteers exposed for a short time in model cardrooms (52), or when exposed to extracts of grain dust (53). However, manifestations of a COPD-like presentation can appear after several years of exposure (5).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that virus infection is capable of overriding inhalation‐induced IgE isotype tolerance and promoting airway allergic responses [ 30]. Endotoxins from the cell wall of Gram‐negative bacteria have been also implicated as etiological agents in the induction of acute and chronic respiratory symptoms, including bronchoconstriction and bronchial hyperreactivity [ 33, 34]. In the current study, we demonstrated that airborne endotoxins, which exist frequently in the subtropical area, can also break inhalation‐induced IgE isotype tolerance and promote airway‐allergic responses.…”
Section: Discussionmentioning
confidence: 99%
“…These effects were again antagonized by propranolol and thus also appear to be mediated by an action on P-adrenoceptors. Eosinophil accumulation in the bronchial lumen is one of the hallmarks of asthma (Horn et al, 1975;Venge, 1985), while neutrophil accumulation is characteristic of other forms of inflammation (Rylander & Haglind, 1986;Thompson et al, 1989). Furthermore, eosinophil and neutrophil accumulation in the airways have been linked to nocturnal asthma (Martin et al, 1991).…”
Section: Discussionmentioning
confidence: 99%